Pengenalan Karakter Islami Anak Usia Dini melalui Pesantren Ramadhan oleh Mahasiswa PIAUD IAI Khozainatul Ulum Blora - Lina, Helina Himmatul Ulya; Nabil, Muhammad; Pradani, Dinda Ayu; Argianti, Safitri Novia (Lembaga Yasin AlSys, 2025)
The Ramadan pesantren program serves as a strategic method for instilling Islamic character values in early childhood through an enjoyable and developmentally appropriate approach. This community service initiative was carried out by students of the Early Childhood Islamic Education (PIAUD) Program at IAI Khozinatul Ulum Blora at RA Assalafiyah Gedongsari, Banjarejo, Blora, in collaboration with the school principal and classroom teachers. The primary objective of the activity was to introduce Islamic character values such as honesty, discipline, responsibility, and love for Allah and the Prophet to 30 young learners. The implementation methods included educational activities such as prayer memorization, daily prayer routines, stories of the Prophet’s exemplary character, and creative Islamic-themed activities. Observations revealed an improvement in children's understanding of Islamic values and the gradual development of positive behavioral habits in daily life. Furthermore, the program provided PIAUD students with hands-on experience in applying early childhood education theories in real-world settings. In conclusion, the Ramadan pesantren program proved to be an effective medium for shaping Islamic character in early childhood through synergistic collaboration between students, teachers, and educational institutions.